Phonation threshold pressure at large asymmetries of the vocal folds. (September 2020) - Lucero, Jorge C.; Pelorson, Xavier; Van Hirtum, Annemie
Abstract: The phonation threshold value of the lung pressure has been interpreted as a measure of ease of phonation and proposed as a diagnostic parameter for vocal health. Therefore, it is important to understand its behavior as a function of laryngeal parameters, particularly in abnormal configurations. This paper compares results from a theoretical model of the vocal folds with measures from a mechanical replica, in the presence of a natural frequency asymmetry. It shows that, at small asymmetry, the threshold pressure increases with the degree of asymmetry, whereas at large asymmetry, the threshold pressure reaches a plateau. Highlights: Comparison of a theoretical model with measures from a mechanical replica. At small asymmetry, the phonation threshold pressure increases with the asymmetry. At large asymmetry, the phonation threshold pressure reaches a plateau. Results indicate caution in the application of phonation threshold pressure as an assessment tool for vocal health.